Effects of Boron on Learning and Behavioral Disorders in Rat Autism Model Induced by Intracerebroventricular Propionic Acid - Alacabey, Nur Akman; Coskun, Devran; Atessahin, Ahmet (Springernature, 2025)
Autism spectrum disorder is a neurodevelopmental disorder in which learning, communication, and social interaction are impaired. Research has sought to minimize the neural impairments associated with autism spectrum disorder and improve the quality of life. Recent studies suggest that boron may benefit nerve cells, with effects varying depending on the dosage. This study explored the impact of boron, administered as boric acid, on behavioral, biochemical, and histopathological parameters in a rat model of autism induced by propionic acid (PPA). Thirty-two male Sprague-Dawley rats were divided into control, autism model, and boron-treated groups. Behavioral tests were conducted pre- and post-PPA induction, with brain tissue analyzed post-euthanasia. Proinflammatory cytokines (tumor necrosis factor alpha (TNF-alpha), interleukin 1 beta (IL-1 beta), interleukin 6 (IL-6)) and brain-derived neurotrophic factor (BDNF) levels were assessed in the hippocampus. Histopathological evaluations were conducted on the hippocampus and cerebellum. Autism model rats displayed impaired learning, elevated BDNF and cytokine levels, microglial and astrocytic activation, and decreased Purkinje cell count. The boron-treated groups showed improvements, particularly with the 4 mg/kg dose. This dose enhanced learning and social interaction, reduced proinflammatory cytokine levels, prevented microglial and astrocytic activation, and increased Purkinje cell count. Boron treatment exhibited neuroprotective potential, ameliorating autism spectrum disorder deficits by modulating cytokines, BDNF, microglia, and astrocytes, with low doses yielding pronounced effects.
Keywords: Autism model; Behavioral deficits; Boron; Learning impairments; Neuroprotective action